Summary of Georgia's Bobwhite Quail Initiative 2000-2005. - Reggie E. Thackston; Chris D. Baumann; Bobby T. Bond; Mark D. Whitney (National Quail Symposium Proceedings, 2017)
Georgia’s Bobwhite Quail Initiative (BQI) has been a proactive effort to restore and improve habitat for northern bobwhite (Colinus virginianus; hereafter bobwhite) on private lands across a 15 county area of Georgia’s Upper Coastal Plain. Secondary objectives included improving habitat for certain songbirds, quail hunting and wildlife viewing. The BQI provided landowners/managers (Cooperators) with technical assistance, and through a competitive process, financial incentives for bobwhite habitat management. The Georgia General Assembly and Department of Natural Resources (DNR) Board initiated BQI in 1998 in response to hunter/constituent concern over declining bobwhite populations; and the Georgia DNR Wildlife Resources Division began implementation in 1999. Funding for BQI was provided through state appropriations, including funds generated through the sale of BQI vehicle license plates. Habitat incentive payments and practice options were modified gradually to increase Cooperator participation and to better integrate bobwhite management with commercial agriculture and forestry. Research and monitoring indicated positive impacts of habitat practices on bobwhites and certain songbirds. The BQI generated many additional benefits including leveraged funding for management and research; youth quota quail hunts; and increased educational outreach regarding the bobwhite decline and effective restoration techniques. A Cooperator survey indicated high customer satisfaction and a strong perception that BQI practices have improved bobwhite and songbird populations, as well as the environmental condition on Cooperator farms. The BQI showed that: 1) bobwhite numbers can be increased on working farm and forestlands, and 2) adequate levels of economic incentives and qualified technical staff are essential for success.
Keywords: Colinus virginianus; farmland; forestland; Georgia; incentives; landowners; northern bobwhite; Upper Coastal Plain